ANALISIS PENGARUH KEGIATAN SOSIALISASI PERPAJAKAN DAN PEMERIKSAAN PAJAK TERHADAP PENERIMAAN PPH PASAL 25/29 WAJIB PAJAK BADAN PADA KPP PRATAMA MEDAN PETISAH - Sihite, Desima R.; Sembiring, Yan Christin Br; Sitanggang, Abdonsius (Jurnal Ilmiah Akuntansi (JIMAT), 2023)
This study aims to find out how to analyze the influence of tax socialization activities and tax audits on income tax revenues article 25/29 for corporate taxpayers at KPP Pratama Medan Petisah. The population in this study is the number of taxpayers who are active and registered at KPP Pratama Medan Petisah from 2015-2022. This study uses primary and secondary data obtained by direct surveys to the field by distributing questionnaires to corporate taxpayers. The data analysis technique used in this study is a descriptive data analysis technique, namely describing and interpreting data according to existing facts.Based on the discussion of the research results obtained, it can be concluded that tax socialization activities at KPP Pratama Medan Petisah partially have a significant positive effect on tax revenues. Tax audit at KPP Pratama Medan Petisah has a significant positive effect on tax revenues. There is a positive influence on the receipt of income tax articles 25/29 for corporate taxpayers. simultaneously tax socialization and tax audit have a positive and significant effect on tax revenues. We can see that the three variables have a positive and significant influence. This means that the more often (positive) tax socialization and tax audit activities are carried out, the income tax revenue article 25/29 will also increase.